2010
DOI: 10.1016/j.yexcr.2010.06.014
|View full text |Cite
|
Sign up to set email alerts
|

MIST1 regulates the pancreatic acinar cell expression of Atp2c2, the gene encoding secretory pathway calcium ATPase 2

Abstract: MIST1 is a transcription factor expressed in pancreatic acinar cells and other serous exocrine cells. Mice harboring a targeted deletion of the Mist1 gene (Mist1−/−) exhibit alterations in acinar regulated exocytosis and aberrant Ca2+ signaling that are normally controlled by acinar cell Ca2+-ATPases. Previous studies indicated that total sarcoendoplasmic reticulum Ca2+-ATPases (SERCA) and plasma membrane Ca2+-ATPases (PMCA) remained unaffected in Mist1−/− acinar cultures. Therefore, we have assessed the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 28 publications
1
46
1
Order By: Relevance
“…Studies to date have focused on the direct transcriptional targets of MIST1 and have identified several genes involved in acinar cell biology, including Gjb1 (encodes Cx32), Atp2c2 (encodes SPCA2), Rab3d, and Rab26 (16,21,43,48). The fact that all of these genes can be linked to acinar cell exocytosis has led to a model in which MIST1 acts as a scaling factor, a type of transcription factor that enhances rather than initiates gene expression of a number of genes associated with a particular cell function (36).…”
Section: Discussionmentioning
confidence: 99%
“…Studies to date have focused on the direct transcriptional targets of MIST1 and have identified several genes involved in acinar cell biology, including Gjb1 (encodes Cx32), Atp2c2 (encodes SPCA2), Rab3d, and Rab26 (16,21,43,48). The fact that all of these genes can be linked to acinar cell exocytosis has led to a model in which MIST1 acts as a scaling factor, a type of transcription factor that enhances rather than initiates gene expression of a number of genes associated with a particular cell function (36).…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that both MIST1 and its Drosophila ortholog, DIMMED, prefer binding to palindromic CATATG or CAGCTG E boxes, usually located within the first kilobase of the first intron of target genes (Park et al 2008;Garside et al 2010;Tian et al 2010;Direnzo et al 2012;Hadzic et al 2015). Using the ChIP-seq analysis of MIST1 binding to acinar cell genomic DNA, we analyzed the location of the significant peaks in our list of putative target genes.…”
Section: Ectopic Expression Of Mist1 In Other Cell Types Phenocopies mentioning
confidence: 94%
“…MIST1 expression is a feature of all serous exocrine cells (Lemercier et al, 1997;Pin et al, 2000). Recent work has begun to identify the molecular targets that it scales up to establish a high-capacity polarized secretory apparatus (Capoccia et al, 2013;Direnzo et al, 2012;Garside et al, 2010;Jia et al, 2008;Johnson et al, 2004;Pin et al, 2001;Rukstalis et al, 2003;Tian et al, 2010). For example, RAB3D has been identified as a target in both pancreatic and gastric exocrine cells (Johnson et al, 2004;Tian et al, 2010).…”
Section: Introductionmentioning
confidence: 99%